AGREEMENTS TO AVOID DOUBLE TAXATION, PERMANENT ESTABLISHMENTS, ITS DOCTRINAIRE RANGE - Santa Cruz Miranda, Adolfo (2015)
In the previous edition of Quipukamayoc Magazine, Vol. 22 No. 42, July-December 2014, was published the first installment of the topic we called “The Internatio-nal Tax and Agreements to avoid double taxation”. We defined the legal scope of “International treaties set out in articles Nos. 55 to 57 of the Political Constitution of Peru and developed the study of international tax treaties called “Agreements to avoid double taxation” (hereinafter CDI). We had the essential task in this first work, to analyze of the causes of international juridical double taxation and bilateral corrections established by the CDI under agreements among countries. The analysis incorporated comments on the meaning of the two “Framework agreements to avoid double taxation”, developed at the international level, particularly the most used by our country, “The OECD Model Convention Framework” developed by the Organization for Economic Cooperation and Economic Development. This Institution under the so-called “G-20” incorporates the main countries of the world economically.